Quadratic Equations 2x²-5x-3=0Pls Answer Fast Then Only I Will Mark Brainlest Answer Will Be Right About the author Everleigh
Answer: Step-by-step explanation: Here, we have ⇒ 2x² – 5x + 3 = 0 Dividing equation by 2, we get ⇒ x² – 5/2x + 3/2 = 0 Shifting the constant term on RHS ⇒ x² – 5/2x = – 3/2 Adding (1/2 coefficient of x)² on both sides ⇒ (x – 5/4)² = 25/16 – 3/2 ⇒ (x – 5/2)² = 1/16 ⇒ x – 5/4 = ± 1/4 or x = 5/4 – 1/4 = 4/4 ⇒ x = 3/2, 1 Hence, the roots of the equation 2x² – 5x + 3 = 0 are 3/2 and 1. Reply
Answer: [tex]2x {}^{2} – 6x + x – 3 \\ 2x(x – 3) + 1(x – 3) \\ (2x + 1)(x – 3)[/tex] Hence zeroes are = 3,-1/2 Reply
Answer:
Step-by-step explanation:
Here, we have
⇒ 2x² – 5x + 3 = 0
Dividing equation by 2, we get
⇒ x² – 5/2x + 3/2 = 0
Shifting the constant term on RHS
⇒ x² – 5/2x = – 3/2
Adding (1/2 coefficient of x)² on both sides
⇒ (x – 5/4)² = 25/16 – 3/2
⇒ (x – 5/2)² = 1/16
⇒ x – 5/4 = ± 1/4 or x = 5/4 – 1/4 = 4/4
⇒ x = 3/2, 1
Hence, the roots of the equation 2x² – 5x + 3 = 0 are 3/2 and 1.
Answer:
[tex]2x {}^{2} – 6x + x – 3 \\ 2x(x – 3) + 1(x – 3) \\ (2x + 1)(x – 3)[/tex]
Hence zeroes are = 3,-1/2